Control of morphologies and properties of zinc oxide nanorod arrays by slightly adjusting their seed layers. (5th October 2016) - Du, Li-Xia; Jiao, Yang; Niu, Si-Ying; Miao, Hui; Yao, He-Bao; Wang, Kai-Ge; Hu, Xiao-Yun; Fan, Hai-Bo
A simple method for controllable growth of zinc oxide nanorod arrays by adjusting preparation conditions of their seed layers is studied. Mole ratio of zinc acetate to diethanol amine, concentration of the two chemicals in the solution, and addition of polyethylene glycol in the solution are identified as three key parameters that have a great influence on microstructure of the seed layers. Surface roughness and uniformity in thickness of the seed layer are found as main factors that determine the nanorod arrays' morphologies and alignments. Average diameter of the nanorods can be tuned from 106 to 336 nm; spacial distribution density of the nanorods is effectively controlled by adding polyethylene glycol. Advantage of this simple method lies in two aspects: First, it ensures that all the nanorod arrays have same chemical compositions as their morphologies change. Second, the controlled morphologies of zinc oxide nanorod arrays can significantly tune the hydrophobic properties. As demonstrated in their hydrophobic properties measurement, the static contact angle of water on their top surfaces can be finely tuned from 127° to 143°.